1977
DOI: 10.1111/j.1365-2621.1977.tb01212.x
|View full text |Cite
|
Sign up to set email alerts
|

VOLATILE CONSTITUENTS OF CANTALOUPE, Cucumis melo, AND THEIR BIOGENESIS

Abstract: The volatile emanations of cultivars of muskmelon were isolated by three procedures: direct sampling of melon cavity gases via a septumsealed glass probe cemented to the melon, entrapment of large volumes of headspace gas on porous polymer traps, and steam distillationextraction of pieces of melon fruit tissue. Essences were subjected to gas chromatographic analysis in high resolution wall-coated open-tubular glass capillary columns. Identifications were based on mass spectra, gas chromatographic retentions, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1

Year Published

1978
1978
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 11 publications
1
30
1
Order By: Relevance
“…Other esters often showed comparable variation. Yabumoto and Jennings (1977) observed significant differences in the concentration of ethyl 2-methylbutanoate, as well as ethyl 2-methylpropanoate, among fruits showing only slight differences in maturity. Horvat and Senter (1987) and later Wang et al (1996) showed that major changes in aroma composition occur just before abscission of the fruit from the vine.…”
Section: Resultsmentioning
confidence: 83%
“…Other esters often showed comparable variation. Yabumoto and Jennings (1977) observed significant differences in the concentration of ethyl 2-methylbutanoate, as well as ethyl 2-methylpropanoate, among fruits showing only slight differences in maturity. Horvat and Senter (1987) and later Wang et al (1996) showed that major changes in aroma composition occur just before abscission of the fruit from the vine.…”
Section: Resultsmentioning
confidence: 83%
“…The AEDA indicated that methyl 2-methylbutanoate and ethyl 2-methylpropanoate were the most intense odorants of the ester fraction. Other volatile esters, identified by Yabumoto et al (1977), seemed to be of minor importance, since they were lacking in the aromagram.…”
Section: Discussionmentioning
confidence: 96%
“…Approximately 100 compounds have been identified in the volatile fraction of muskmelons (Maarse and.Visscher, 1987) and as revealed by the aroma profile, (Z)-6-nonenal and some volatile esters have been indicated (Kemp et al, 1972;Yabumoto et al, 1977) to be most responsible for the melon-like and fruity notes, respectively.…”
mentioning
confidence: 99%
“…Among these compounds, volatile esters were quantitatively the most important and therefore represent key contributors to the aroma [68]. The linear saturated and unsaturated aldehydes seem to originate from the degradation of linolenic and linoleic acids [26,32,33,67].…”
Section: Melon (Cucumis Melo)mentioning
confidence: 99%
“…The extraction technique can play an important role in the recovery of volatiles, resulting in different profiles of volatiles for the same variety [67]. The direct extraction of Cucumis melo L. var.…”
Section: Melon (Cucumis Melo)mentioning
confidence: 99%